Thoracic interfascial plane block for multimodal analgesia after breast lumpectomy - Kim, Yeojung; Oh, Chahyun; Youn, Sookyoung; Yun, Sangwon; Park, Hyunwoo; Lee, Wonhyung; Kim, Yoon-Hee; Ko, YoungKwon; Hong, Boohwi (Anesthesia and pain medicine (Korean society of anesthesiologists), 2019)
Background: Thoracic interfascial plane block is useful as a component of multimodal analgesia in patients undergoing mastectomy. However, multimodal analgesia tends not to be provided during lumpectomy as it is one of the less aggressive procedures among breast cancer surgeries. Therefore, we investigated the effects of thoracic interfascial plane block as more effective analgesia after breast lumpectomy. Methods: Forty six patients (20–80 years old, female) with breast cancer scheduled to undergo lumpectomy were randomly assigned to two groups. Postoperative pain control in the control group consisted only of intravenous patient-controlled analgesia (PCA). In the block group, intravenous PCA was used after serratus intercostal fascial plane block and pecto-intercostal fascial plane block. The primary outcome was the 24 h cumulative postoperative fentanyl consumption. Pain severity, additional rescue analgesic requirement, side effects, and patient satisfaction were also evaluated. Results: Postoperative fentanyl consumption in the block group was significantly reduced compared with the control group (median, 88.8 [interquartile range, 48.0, 167.6] vs. 155.2 [88.8, 249.2], P = 0.022). The pain score was significantly lower in the block group only in the post-anesthesia care unit (2.9 ± 1.8 vs. 4.3 ± 2.3, P = 0.022). There were no differences in the incidence of postoperative nausea and vomiting and the requirement for additional analgesics between the groups. The satisfaction score was significantly higher in the block group. Conclusions: Thoracic interfascial plane block after lumpectomy reduces opioid usage and increases patient satisfaction with postoperative pain control. Thoracic interfascial plane block is useful for multimodal analgesia after lumpectomy. KCI Citation Count: 0